Biochemical consequences of two clinically relevant ND-gene mutations in Escherichia coli respiratory complex I - Franziska Nuber (Nature Portfolio, 2021)
Abstract NADH:ubiquinone oxidoreductase (respiratory complex I) plays a major role in energy metabolism by coupling electron transfer from NADH to quinone with proton translocation across the membrane. Complex I deficiencies were found to be the most common source of human mitochondrial dysfunction that manifest in a wide variety of neurodegenerative diseases. Seven subunits of human complex I are encoded by mitochondrial DNA (mtDNA) that carry an unexpectedly large number of mutations discovered in mitochondria from patients’ tissues. However, whether or how these genetic aberrations affect complex I at a molecular level is unknown. Here, we used Escherichia coli as a model system to biochemically characterize two mutations that were found in mtDNA of patients. The V253AMT-ND5 mutation completely disturbed the assembly of complex I, while the mutation D199GMT-ND1 led to the assembly of a stable complex capable to catalyze redox-driven proton translocation. However, the latter mutation perturbs quinone reduction leading to a diminished activity. D199MT-ND1 is part of a cluster of charged amino acid residues that are suggested to be important for efficient coupling of quinone reduction and proton translocation. A mechanism considering the role of D199MT-ND1 for energy conservation in complex I is discussed.